Uncertainties in age- and gender-based health risk assessment for recreational bathing: Arsenic in Del Azul stream, Argentina - Peluso, Fabio Oscar (2015)
The aim of this study was to assess the risk associated with recreational bathing at Del Azul stream, Argentina, a water course naturally containing Arsenic. It represents a case study on the carcinogenic risk for bathers and on how the risk varies among age groups and genders, analyzing the uncertainties of the model input variables and the risk quantification technique. The risk was probabilistically estimated with the 2D Monte Carlo method considering four age groups (5, 10, 15, and 20 years old) and separate exposure routes: accidental water intake, skin contact, and the two combined. Although in all the studied groups the risk levels were within safety limits, differences in risk values were observed among age groups and genders. Accidental water intake during bathing was the most risky exposure route. The risk decreased with age and it was higher in males than in females, with larger differences between the two older age groups. This could be attributed to the difference in the accidental water intake rate associated with the daily duration of the bathing event, which varied according to age and gender.